Mental health prevention and control management facilities and personnel in the mainland of China, 2020: a cross-sectional survey - Xiamin WU; Ning MA; Runzi CHEN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the status quo of mental health prevention and control management facilities (MHPCMFs) up to 2020 in the mainland of China for providing evidence to the development of infrastructure and strategies of mental health prevention and control. MethodsThe information on the status of MHPCMFs at province, municipality/prefecture, and district/county level in 31 province-level administrative divisions (PLADs) across China was collected during May - June 2021 using a questionnaire designed by The National Mental Health Program Office. The organizational system and personnel of the MHPCMFs were analyzed. ResultsBy the end of 2020, totally 3 315 MHPCMFs were established at all PLADs, 99.70% of 333 municipalities/prefectures and 99.73% of 2960 districts/counties in the mainland of China. Of the established MHPCMFs, only 7 were independent legal entities and 3 308 were affiliated to health institutions or government departments, with 77.42% of the province-level and 76.51% of the municipality/prefecture-level MHPCMFs affiliated to mental health medical facilities and 61.25% of the county/district-level MHPCMFs affiliated to centers for disease control and prevention. The total number of personnel in the established MHPCMFs was 9 846, among which 34.43% were public health physicians, 17.79% were registered nurses, and 15.57% were psychiatrists and there were a few psychological therapists/counselors and social workers in the MHPCMFs. The average number of personnel engaged in services provided by the MHPCMFs was 0.7 for 100 000 population. The median number of staff was 6, 3 and 2 for the MHPCMFs at province-, municipality/prefecture-, and county/district-level, respectively. ConclusionThe management system for mental health promotion has been developed nationwide and at various administrative level across the mainland of China, but the established MHPCMFs were lack of mental health professionals, suggesting that professional allocation in the MHPCMFs needs to be improved.